2014
DOI: 10.7326/m13-2316
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Harms of Computed Tomography Lung Cancer Screening Strategies: A Comparative Modeling Study for the U.S. Preventive Services Task Force

Abstract: Background The optimal screening policy for lung cancer is unknown. Objective To identify efficient CT-screening scenarios where relatively more lung cancer deaths are averted for fewer CT screens. Design Comparative modeling study using 5 independent models. Data Sources The National Lung Screening Trial, the Prostate, Lung, Colorectal and Ovarian trial, the Surveillance, Epidemiology, and End Results program, and U.S. Smoking History Generator. Target Population U.S. cohort born in 1950. Time Horiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
401
3
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 399 publications
(413 citation statements)
references
References 46 publications
6
401
3
3
Order By: Relevance
“…134 A more recent synthesis of five independent US models, again founded on the most recent clinical evidence, yielded predicted gains of between 0.02 and 0.09 life-years per person screened, depending on assumptions relating to screening frequency and subjects' smoking history. 135 …”
Section: Predicted Outcomesmentioning
confidence: 99%
“…134 A more recent synthesis of five independent US models, again founded on the most recent clinical evidence, yielded predicted gains of between 0.02 and 0.09 life-years per person screened, depending on assumptions relating to screening frequency and subjects' smoking history. 135 …”
Section: Predicted Outcomesmentioning
confidence: 99%
“…However, the Cancer Intervention and Surveillance Modeling Network (CISNET) recently reported an analysis that includes eligibility criteria and screening intervals. 40 In conclusion, we estimate that screening with low-dose CT for lung cancer as performed in the NLST costs less than $100,000 per QALY gained. The determination of whether screening performed outside the trial will be cost-effective will depend on exactly how screening is implemented.…”
Section: Discussionmentioning
confidence: 99%
“…The colorectal cancer screening module has recently undergone an extensive validation exercise that replicates four rcts (submitted for publication), and work has begun to evaluate cervical cancer screening against rcts. To ensure the external validity of lung cancer low-dose computed tomography screening, OncoSim results were compared with those from the U.S. National Lung Screening Trial (nlst) and the relevant cisnet models 24 . Using simulated trial characteristics and a cohort matched to the nlst, outcomes similar to those reported from the trial were achieved 3 .…”
Section: Discussionmentioning
confidence: 99%